2021
DOI: 10.1063/5.0037344
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic levitation of a Mie sphere using a 2D transducer array

Abstract: Most acoustic levitation techniques are limited to objects smaller than half the wavelength. To overcome this limit, different strategies have been proposed for suspending macroscopic objects in mid-air. Two approaches to levitate spherical and non-spherical macroscopic objects have been recently presented: the acoustical virtual vortices and the boundary hologram method. However, the former approach places high demands on the available hardware due to the mandatory high switching rate while the latter uses a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…Despite the existence of advanced simulation techniques for droplet evaporation, many phenomena remain challenging to explain. Hence, depending on the study's actual targets, it may be essential to develop acoustic suspension technology, such as overcoming limits of droplet size in a levitator [54] and using advanced sensors to measure small droplet evaporation [112] , [113] , conducting the appropriate experiments, or verify the evaporation model. There are several potential applications for acoustic suspension technology, such as controlling droplet shape, size, fragmentation, coalescence, detecting droplet viscosity and surface tension, etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the existence of advanced simulation techniques for droplet evaporation, many phenomena remain challenging to explain. Hence, depending on the study's actual targets, it may be essential to develop acoustic suspension technology, such as overcoming limits of droplet size in a levitator [54] and using advanced sensors to measure small droplet evaporation [112] , [113] , conducting the appropriate experiments, or verify the evaporation model. There are several potential applications for acoustic suspension technology, such as controlling droplet shape, size, fragmentation, coalescence, detecting droplet viscosity and surface tension, etc.…”
Section: Discussionmentioning
confidence: 99%
“…The levitated droplets are tiny and usually limited to half of the wavelength [52] , [53] , [54] , , where is the sound velocity depending on the ambient temperature, while is the frequency [55] . Therefore, high temperatures can be implicitly influenced the performance of the levitator [22] , [56] .…”
Section: Fundamentals Of the Levitated Droplet In Acoustic Filedmentioning
confidence: 99%
“…This work has shown that, for particular sizes, Mie particles can be stably levitated by plane-waves in pressure anti-nodes, but off-axis (in contrast to Rayleigh particles, which levitate on-axis and in pressure nodes). More generally, the stable levitation of Mie particles has focused, especially on the experimental side, on shaping the incident wavefront via computational methods [54][55][56][57][58].…”
Section: Scattering Forces On Objects Without Sound-induced Deformationsmentioning
confidence: 99%
“…Although a parallel analysis has been proposed and analyzed theoretically for ray acoustics [161,162], the range of particle sound absorbency and beam conditions that permit stable levitation appears to be very small. Additionally, current experimental techniques for acoustic levitation in the Mie limit have so far successfully levitated only objects of size smaller than three wavelengths, far from the regime where such an analysis would be appropriate [54,55,163,164]. Nevertheless, the principle of redirected acoustic momentum flux can be used to levitate and exert forces on particles with size of order λ.…”
Section: Connections To Optical Radiation Forcesmentioning
confidence: 99%
“…Although objects larger than the wavelength have been levitated, controlled levitation has been limited to sub-wavelength sample size with few exceptions, such as spheres and cubes. Previously larger-than-wavelength sample levitation was achieved using the sample as reflector [6], a multifrequency high aperture vortex trap [7], or by direct optimization of the radiation force acting on a sphere [8]. Near-field levitation achieves larger-than-wavelength levitation in close proximity to the transducer.…”
Section: Introductionmentioning
confidence: 99%